Stain-free identification of tissue pathology using a generative adversarial network to infer nanomechanical signatures. Issue 22 (23rd September 2021) - Neary-Zajiczek, Lydia; Essmann, Clara; Rau, Anita; Bano, Sophia; Clancy, Neil; Jansen, Marnix; Heptinstall, Lauren; Miranda, Elena; Gander, Amir; Pawar, Vijay; Fernandez-Reyes, Delmiro; Shaw, Michael; et al.
Abstract : Sample-wide elastic modulus is inferred from unstained images of frozen liver tissue sections. Distribution parameters can predict tissue pathology for use as an intraoperative diagnostic tool. Abstract : Intraoperative frozen section analysis can be used to improve the accuracy of tumour margin estimation during cancer resection surgery through rapid processing and pathological assessment of excised tissue. Its applicability is limited in some cases due to the additional risks associated with prolonged surgery, largely from the time-consuming staining procedure. Our work uses a measurable property of bulk tissue to bypass the staining process: as tumour cells proliferate, they influence the surrounding extra-cellular matrix, and the resulting change in elastic modulus provides a signature of the underlying pathology. In this work we accurately localise atomic force microscopy measurements of human liver tissue samples and train a generative adversarial network to infer elastic modulus from low-resolution images of unstained tissue sections. Pathology is predicted through unsupervised clustering of parameters characterizing the distributions of inferred values, achieving 89% accuracy for all samples based on the nominal assessment ( n = 28), and 95% for samples that have been validated by two independent pathologists through post hoc staining ( n = 20). Our results demonstrate that this technique could increase the feasibility of intraoperative frozen section analysis for use during resection surgery and improve patient outcomes.